Focus on Forms or Focus on Form Instruction in the Context of English as a Foreign Language - Purnomo, Windy Wahju (JLA (Jurnal Lingua Applicata), 2025)
The Focus on forms and focus on form are two distinguishable approaches to language teaching. The focus on forms emphasizes on the explicit instruction of the grammatical structure, vocabulary, and pronunciation. This approach of teaching is commonly taught through separate drills and exercises. Meanwhile, the later approach is commonly applied in communicative language teaching. Some studies reveal that either focus on forms or focus on form may be beneficial for language learners in a particular context.  This  article comprehensively analyzes the effectiveness of classroom instruction applying focus on form and focus on forms. Thirty five journal articles were reviewed and analyzed to describe the pedagogic activities of focus on form and focus on forms, the psycholinguistic dimensions of focus on form, the impacts of feedback provision on focus on form, and the positive impacts of focus on form on language teaching activities. The finding indicates that applying one approach to teaching, form focus or forms focus instruction will not be effective in attaining the goals. Finally, it can be concluded that both forms focus and form focus are suggested to be practiced simultaneously and be integrated rather than one opposes to the other.